ANALISIS PERBANDINGAN MODEL ALTMAN, MODEL SPRINGATE, DAN MODEL ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN BANK SYARIAH DI INDONESIA - Diyah Santi Hariyani; Agung Sujianto (INVENTORY: JURNAL AKUNTANSI, 2017)
ABSTRACTThe purpose of this research to provide empirical evidence that the Model Altman , Springate , and Zmijewski is the most appropriate model for predicting bankruptcy Islamic Bank in Indonesia . The population in this study are all Islamic banks listed on the Indonesia Stock Exchange . This study uses secondary data from the financial statements of Islamic banks in 2010-2014 . Testing the hypothesis in this study using normality test, homogeneity test, and one way ANOVA test ( different test ) . The results showed that Springate model is the most appropriate model to predict the Islamic banks in Indonesia with an accuracy of 38.00 % , then Model Zmijewski with 28.00 % accuracy rate and Altman with an accuracy of 0.00 % .Keywords : Altman Z-Score Model, Springate S-Score Model, Zmijewski X-Score Model.